Dexmedetomidine hydrochloride as a long-term sedative - Kunisawa T (Dove Medical Press, 2011)
Takayuki KunisawaSurgical Operation Department, Asahikawa Medical University Hospital, Asahikawa, Hokkaido, JapanAbstract: Dexmedetomidine undoubtedly is a useful sedative in the intensive care setting because it has a minimal effect on the respiratory system. Dexmedetomidine infusions lasting more than 24 hours have not been approved since the first approval was acquired in the US in 1999. However, in 2008, dexmedetomidine infusions for prolonged use were approved in Colombia and in the Dominican Republic, and the number of countries that have granted approval for prolonged use has been increasing every year. This review discusses the literature examining prolonged use of dexmedetomidine and confirms the efficacy and safety of dexmedetomidine when it is used for more than 24 hours. Dexmedetomidine was administered at varying doses (0.1–2.5 µg/kg/hour) and durations up to 30 days. Dexmedetomidine seems to be an alternative to benzodiazepines or propofol for achieving sedation in adults because the incidences of delirium and coma associated with dexmedetomidine are lower than the corresponding incidences associated with benzodiazepines and propofol, although dexmedetomidine administration can cause mild adverse effects such as bradycardia. Controlled comparative studies on the efficacy and safety of dexmedetomidine and other sedatives in pediatric patients have not been reported. However, dexmedetomidine seems to be effective in managing extubation, reducing the use of conventional sedatives, and as an alternative for inducing sedation in patients for whom traditional sedatives induce inadequate sedation. Prolonged dexmedetomidine infusion has not been reported to have any serious adverse effects. Dexmedetomidine appears to be an alternative long-term sedative, but further studies are needed to establish its efficacy and safety.Keywords: dexmedetomidine, prolonged sedation, long-term